Oceans and human health-navigating changes on Canada's coasts - Tiff-Annie Kenny; Philippe Archambault; Pierre Ayotte; Malek Batal; Hing Man Chan; William Cheung; Tyler D. Eddy; Matthew Little; Yoshitaka Ota; Claudel Pétrin-Desrosiers; Steve Plante; Julien Poitras; et al. (Canadian Science Publishing, 2020)
Ocean conditions can affect human health in a variety of ways that are often overlooked and unappreciated. Oceans adjacent to Canada are affected by many anthropogenic stressors, with implications for human health and well-being. Climate change further escalates these pressures and can expose coastal populations to unique health hazards and distressing conditions. However, current research efforts, education or training curriculums, and policies in Canada critically lack explicit consideration of these ocean-public health linkages. The objective of this paper is to present multiple disciplinary perspectives from academics and health practitioners to inform the development of future directions for research, capacity development, and policy and practice at the interface of oceans and human health in Canada. We synthesize major ocean and human health linkages in Canada, and identify climate-sensitive drivers of change, drawing attention to unique considerations in Canada. To support effective, sustained, and equitable collaborations at the nexus of oceans and human health, we recommend the need for progress in three critical areas: (i) holistic worldviews and perspectives, (ii) capacity development, and (iii) structural supports. Canada can play a key role in supporting the global community in addressing the health challenges of climate and ocean changes.